Ground-Level Pressing Issues at the Intersection of AI and IP - Kappos, David; Kling, Asa (Science and Technology Law Review, 2021)
Humankind has always sought to solve problems. This impetus has transformed hunters and gatherers into a society beginning to enjoy the fruits of the fourth industrial revolution. As part of the fourth industrial revolution, and the increased computing power accompanying it, the long-theorized concept of artificial intelligence (“AI”) is finally becoming a reality. This raises new issues in myriad fields—from the moral and ethical implications of replacing human activity with machines to who will own inventions created by AI. While these questions are worth exploring, they have already received a fair amount of coverage in popular and theoretical writing. This paper will take a different direction, focusing on the current and near-future issues arising on the ground at the intersection of AI and intellectual property (“IP”). After providing a brief overview of AI, we will analyze legal issues unique to AI, including access to data, patent requirements, open source licenses and trade secrecy. We will then suggest best practices for obtaining and preserving IP protection for AI-related innovations through the United States and European Union IP systems. By addressing these issues, the intellectual property system will be better positioned to do its part in unlocking AI’s immense potential.